2020
DOI: 10.1186/s42400-020-00055-5
|View full text |Cite
|
Sign up to set email alerts
|

Using deep learning to solve computer security challenges: a survey

Abstract: Although using machine learning techniques to solve computer security challenges is not a new idea, the rapidly emerging Deep Learning technology has recently triggered a substantial amount of interests in the computer security community. This paper seeks to provide a dedicated review of the very recent research works on using Deep Learning techniques to solve computer security challenges. In particular, the review covers eight computer security problems being solved by applications of Deep Learning: security-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Our work covers partly the same primary studies, but our work discusses in addition the analysis of object code and the differences of the underlying deep learning architecture while this work focuses on deep neural networks. Computer security issues investigated by deep learning is the topic of the work by Choi et al (2020). Their range of covered topics is much broader.…”
Section: Related Workmentioning
confidence: 99%
“…Our work covers partly the same primary studies, but our work discusses in addition the analysis of object code and the differences of the underlying deep learning architecture while this work focuses on deep neural networks. Computer security issues investigated by deep learning is the topic of the work by Choi et al (2020). Their range of covered topics is much broader.…”
Section: Related Workmentioning
confidence: 99%
“…They match the code blocks by using the regular matching through a huge rule base, which has a large improvement space [10]. With the development of code vectorization, auditing models of machine learning are proposed and optimized [11,12].…”
Section: Code Auditing With Machine Learningmentioning
confidence: 99%
“…For that purpose, we use the chest X-Ray imaging method to study the case in detail where studies revealed that deeper analysis of chest X-Ray found the ability to identify the disease correctly, the specificity of which reaches 90% [9]. Big data, deep learning and artificial intelligence [43] are used in innumerable fields of study, analysis and prediction in the recent times, be it the healthcare sector [10,6,34], security [12,19], recommendation systems [3], surveillance bots [44] or dealing with microscopy images [14] and cardiovascular problems [41]. In this paper, we discuss the various deep learning models and build models that could distinctly classify an X-ray into regular pneumonia, Covid-19 pneumonia or a patient without pneumonia.…”
Section: Introduction Covid-19 (Corona Virus Disease 2019mentioning
confidence: 99%